(untitled) (Journal of Plant Disease Sciences, 2018)
Efficay of seed dresser and foliar spray fungicides tested against the Pod blight complex of soybean under natural field condition during Kharif 2017 at field of AICRP on soybean, Amravati. Results revealed that the highest seed germination recorded in seed treatment with carboxin + thiram (combi product) @ 2g/kg seed while minimum disease index (5.72%), least per cent pod infection (11.06%) and maximum grain yield (1246 kg/ha) registerd in treatment T4- seed treatment with carboxin + thiram @ 2g/kg + foliar spray with thiophanate methyl @ 0.1% at 55 and 75 DAS followed by treatment T5- seed treatment with carbendazim + mancozeb (combi product) @ 2g/kg seed + foliar spray with thiophanate methyl @ 0.1% at 55 and 75 DAS (1139 kg/ha) and treatment T6- seed treatment with Trichoderma + spray with thiophanate methyl @ 0.1% at 55 and 75 DAS (1033 kg/ha).